Growth performance of weaner rabbits fed dried Moringa oleifera leaf meal. (May 2019) - Zendrato, D P; Ginting, R; Warisman,; Siregar, D J S; Putra, A; Sembiring, I; Hamdan,; Ginting, J; Henuk, Y L
Abstract: An experiment was conducted to study growth performane of weaner rabbits fed dried Moringa oeifera leaf meal. Twenty weaner rabbits (New Zealand White breed) with an average live weight of 918.42 ± 6.84g were used to evaluate the growth performance, daily weight gain (DWG), feed convertion ratio (FCR), and income over feed cost (IOFC) of weaner rabbits fed diets containing graded levels of moringa ( Moringa oleifera ) leaf meal (MOLM) in diets. The study lasted for eight weeks.The rabbits were assigned into four treatment groups and five replicates consisting of four rabbits per group in a complete randomised design and fed four diets designated T0, T1, T2 and T3 with 0, 20, 40 and 60% MOLM, respectively. Result showed that the average of feed intake for each treatment T0 ; T1 ; T2 and T3 (g/head/day) were:104.96; 110.06; 109.34; 107.04, DWG (g/head/day):18.87; 22.35; 21.60; 21.5; FCR: 5.57; 4.95; 5.08; 5.06, and IOFC (Rp/head): 57, 012.73; 73, 197.77; 72, 525.36; 74, 435.32, respectively. The statistical analysis indicated that the utilization of MOLM in diets gaves not significantly different (P>0, 05) on the productive performances of weaner rabbits. Utilization of MOLM can be used up to 60% on diets and increased income from diets of weaner rabbits.